في تعلم اللغة العربية والإسلامية لدى طلبة العلوم والتكنولوجيا (CLIL ) تطبيق نموذج تعلم اللغة المتكاملة - Ningsih, Anita Andriya; Munir, Muhammad Mubasysyir (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Science and Technology students at State Islamic Universities in the learning process and the results are certainly not the same as science students at other public universities. In this case the differences are apparent in the scientific integrity of Science and Islam. So that as much as possible scientific theory revolves around Muslim scientific figures and also learning references used in Arabic. In addition to the learning process, in the final project phase, science students also bring up the integration of Islam with their knowledge. CLIL is a new paradigm used in this study with a content base where the implementation of Islamic religious learning uses a series of contents in Arabic learning.  Qualitative research is used as an approach in this research with a descriptive-analysis method. Primary data on CLIL concepts from some literature and secondary data are some articles relevant to this topic. This study found that the CLIL learning model used was Theme-based where Islamic religious learning content was presented as study material and then analyzed in terms of language elements such as sound science, morphology, syntax and semantics. The findings in this study can be concluded that CLIL is an appropriate method in achieving the vision and mission in interrogating science. The suggestions in this study are more detailed in each scientific element so that the results of integration are more optimal and focused.